Implementation of Inquiry Based Electrical and Electronic Instructional Module in Vocational School - Aryanti, Letty; Jalinus, Nizwardi; Yulastri, Asmar (Universitas Pendidikan Ganesha, 2020)
The importance of modules in learning as enhancing student learning outcomes. Thus, it is necessary to conduct a needs analysis for the development of inquiry-based modules in improving student learning outcomes.Thus, through this module students are taught to study independently and think critically. This study aims to conduct a needs analysis of the implementation of inquiry-based learning modules in basic subjects of electricity and electronics. This type of research is a qualitative descriptive study. The respondents chosen in this study were subject teachers and tenth gradeÂ students of Audio Video Engineering in Vocational Schools in Padang, which were 70 students and randomly selected. The instrument used in this study was an observation sheet in the form of a questionnaire (yes-no Question). The results of the study shows that students need inquiry-based modules more than books or other independent teaching materials in which 100% of students answered needing independent teaching materials and 80% of students answered needing modules.